2008
DOI: 10.1021/jp710758q
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of (Ga1-xZnx)(N1-xOx) for Visible-Light-Driven H2 and O2 Evolution in the Presence of Sacrificial Reagents

Abstract: The photocatalytic activity of (Ga1- x Zn x )(N1- x O x ), a solid solution of GaN and ZnO, for H2 and O2 evolution in the presence of methanol and silver nitrate as sacrificial reagents under visible light (λ > 420 nm) is investigated in detail. (Ga1- x Zn x )(N1- x O x ) evolves H2 from an aqueous methanol solution when loaded with nanoparticulate Rh2- y Cr y O3 as a cocatalyst, and evolves O2 from an aqueous silver nitrate solution without a cocatalyst. Structural analyses indicate that the H2 evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 32 publications
2
91
0
Order By: Relevance
“…The results are summarized in the Supplementary Material (section S2). The band gap values derived from the UV-visible spectra were in agreement with those available in the literature [9,31].…”
Section: Characterization Of Oxynitridessupporting
confidence: 87%
See 1 more Smart Citation
“…The results are summarized in the Supplementary Material (section S2). The band gap values derived from the UV-visible spectra were in agreement with those available in the literature [9,31].…”
Section: Characterization Of Oxynitridessupporting
confidence: 87%
“…However, this co-catalysts/semiconductor system is less effective in the methanol photocatalytic reforming reaction [31]. High temperature reduction of the metal precursor [32] in H 2 is one of the most commonly used methods to prepare supported metal catalysts, but it is believed unsuitable for oxynitrides because of their limited thermal stability compared to oxides [33].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we conducted a systematic analysis of the dependence of the activities of GaN:ZnO for H 2 and O 2 evolution half reactions in the presence of sacrificial reagents on structural properties, and the results are compared to the data for overall water splitting. 53 GaN:ZnO evolved H 2 steadily from an aqueous methanol solution when loaded with a proper H 2 evolution cocatalyst, and evolved O 2 from an aqueous silver nitrate solution without the aid of a cocatalyst. Structural analyses indicated that the H 2 evolution activity depends strongly on the crystallinity and composition of GaN:ZnO, while the rate of O 2 evolution is proportionally related to the specific surface area.…”
Section: Ganmentioning
confidence: 99%
“…Rh2-xCrxO3 was tested recently as nanoparticles. 35), 39) Many nitrides and oxynitrides belonging to various structuretypes have been tested separately for photoreduction and photooxydation reactions using sacrificial agents, respectively with methanol (electron donor) and silver nitrate (electron acceptor). For example, TaON and CaTaO2N manifest an activity for photoreduction and Ta3N5 and TaON, a strong activity for photooxydation.…”
Section: Visible-light-driven Photocatalysismentioning
confidence: 99%